MODELS OF INDIVIDUAL LINEAR SIZES REQUIRED FOR CONSTRUCTION OF THE CORRECT FORM OF DENTAL ARCH IN MESOCEPHALIC-GIRLS IN DEPENDENCE ON THE FEATURES OF ODONTOMETRIC AND CEPHALOMETRIC INDICATORS - Петрушанко, Т.О.; Гунас, І.В.; Марченко, А.В. (World of Medicine and Biology, 2017)
Aim of our work – develop and conduct a regression analysis models of individual linear sizes required for construction of the correct form of dental arch in mesocephalic-girls in dependence on the features of odontometric and cephalometric indicators.Materials and methodsPrimary indices of teeth size and heads of mesocephalic-girls from Podillia with orthognathic bite (n = 16, determined by 11 points by M. G. Bushan et al.) were obtained from the data bank of the research center of the Vinnitsa National Medical University named after Pirogov within the framework of the agreement on creative cooperation between Vinnitsa National Medical University named after Pirogov and Higher state educational institution of Ukraine "Ukrainian Medical Dentistry Academy" (Contract № 1 dated by 05.01.2015).For this study used dental cone-beam tomography - Veraviewepocs 3D, Morit (Japan). In upper and lower incisors, canines, small and first large molar teeth measured: the length of the tooth; root length in vestibular-tongue and mesio-distal projections; mesio-distal size of the crown; vestibular- tongue size; width dentin-enamel limit in mesio-distal direction; width dentin-enamel limit in vestibular- tongue direction. As in previous studies with comparison of computer-tomographic metric characteristics of similar teeth right and left sides, significant differences or trends have not been identified by us, in subsequent studies we used average values of corresponding teeth on the upper and lower jaws.Measurements of cephalometric sizes conducted by soft measuring tape and a large compass with life-size scale systems by Martin.Construction of linear regression models sizes, needed to build the correct form of the dental arch depending on the characteristics of odontometric and cephalometric indicators performed using the statistical software package licensed "Statistica 6,0".Results. DiscussionsOf 18 possible linear sizes necessary for constructing the correct form of the dental arc in mesocephalic-girls with orthognathic bite, based on the odontometric and cephalometric characteristics, all 18 reliable models (determination coefficient from 0.771 to 0.994) were constructed. Constructed models with a determination coefficient more than 0.6 most often include the size of teeth (61.2%, of which 21.4% accounted for the upper incisors, 10.2% for the lower incisors, 7.1% for the upper canine, 8 , 2% - on the lower canine, 3.1% - on the upper small corner teeth, 10,2% - on the lower small corner teeth, 1,0% - on the upper first large angular teeth) than cephalometric indices (38,8 %). Among the sizes of the upper and lower incisors, canines, small and first large angular teeth, the most frequent indicators are the following: mesiodistal dimensions of the crown of the teeth (19.4%, of which 8.2% on the upper jaw); the vestibule-tongue size of the crown of the teeth (11.2%, of which 6.1% on the upper jaw) and the length of the teeth (11.2%, of which 5.1% on the upper jaw). Among the cephalometric indices models most often include: ear diameter (5,1%); average face width (3.1%); mouth width (3.1%); distance from auricular point to subnazion (3.1%).The results of our mathematical modeling of the individual linear sizes necessary for constructing the correct form of the dental arc in mesocephalic-girls with orthognathic bite, depending on the characteristics of odontometric and cephalometric indices, require a revision of conventional orthodontic schemes. This, in turn, will increase the effectiveness of orthodontic treatment in each clinical case and will avoid abnormal and unexpected errors.
Keywords: mesocephalic-girls with orthognathic bite; regression analysis; odontometric and cephalometric characteristics; correct form of the dental arc